Alteration and the Function of Intestinal Microbiota in High-Fat-Diet- or Genetics-Induced Lipid Accumulation - Qiao, Fang; Tan, Fang; Li, Ling-Yu; Lv, Hong-Bo; Chen, Liqiao; Du, Zhen-Yu; Zhang, Mei-Ling (Frontiers in Microbiology, 2021)
Diet and host genetics influence the composition of intestinal microbiota, yet few studies have compared the function of intestinal microbiota in diet- or genotype-induced lipid deposition, which limits our understanding of the role of intestinal bacteria in metabolic disorders. The lipid accumulation in wide-type (WT) zebrafish fed with control (CON) or high-fat (HF) diet, and two gene-knockout zebrafish lines (cpt1b-/- or pparab-/-) fed with control diet was measured post a four-week feeding experiment. The intestinal microbiota composition of these groups was investigated by using 16S rRNA gene sequencing (DNA-based) and 16S rRNA sequencing (RNA-based), respectively. The HF diet or deficiency of two genes induced more weight gain and higher triglyceride (TG) content in liver compared with their control group. 16S rRNA gene sequencing (DNA-based) indicated the decreased abundance of Proteobacteria in HF group compared with CON, but there was no significant difference in bacterial α diversity among treatments. 16S rRNA sequencing (RNA-based) confirmed the decreased abundance of Proteobacteria and the bacterial α diversity in HF group compared with CON. Deficiency of cpt1b or pparab showed less change in microbiota composition compared with their WT group. Intestinal microbiota of each group was transferred to germ-free zebrafish and the quantification of Nile red staining indicated that intestinal microbiota of HF group induced more lipid accumulation compared with CON, while intestinal microbiota of cpt1b-/- and pparab-/- zebrafish did not. The results showed that RNA-based bacterial sequencing revealed more bacterial alteration than DNA-based bacterial sequencing. HF diet had a more dominate role in shaping gut microbiota composition to induce lipid accumulation compared with the gene-knockout of cpt1b or pparab in zebrafish and the transplant of intestinal microbiota from HF-fed fish induced more lipid deposition in germ-free zebrafish. Together, these data suggested that high-fat-diet exerted more dominant role over the deletion of cpt1b or pparab on the intestinal bacterial composition, which corresponded to lipid accumulation.